Bowel obstruction caused by a gallstone (gallstone ileus) - Amorín Cal, Raúl (Cirugía del Uruguay, 2020)
A case of biliary ileus with pneumatosis of the bile ducts, is reported. Pre-operative preparation and surgical approach, are discussed.